ADRENAL VASCULAR (ENDOTHELIAL) CYST: A CASE REPORT AND LITERATURE REVIEW - EUAPITAKSAKUL, Wattanawan; TAWIPORNCHAI, Surasuk; CHAIWUN, Benjaporn (The ASEAN Journal of Radiology, 2023)
Adrenal vascular (endothelial) cysts are rare adrenal lesions. Herein, we reported a case of adrenal endothelial cyst in a 30-year-old pregnant woman. The patient had a 10-day history of left upper quadrant pain. Abdominal ultrasonography and computed tomography showed a huge hemorrhagic cystic lesion superior to the left kidney. Calcified cyst wall with internal septae was also noted. The microscopic examinations revealed multiloculated cysts lined focally by benign flattened endothelial cells. The general feature, differential diagnosis, pathogenesis, and management of adrenal cysts were discussed.